2017
DOI: 10.1111/1556-4029.13570
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of Postcranial Sex Estimation Methods for a Guatemalan Population

Abstract: This study tests whether postcranial sex estimation methods generated from Hispanic, and mainly Mexican samples, can be successfully applied to other increasingly common migrant populations from Central America. We use a sample of postcranial data from a modern (1980s) Guatemalan Maya sample (n = 219). Results indicate a decrease in classification accuracies for previously established univariate methods when applied to the Guatemalan study sample, specifically for males whose accuracies ranged from 30 to 84%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In the case of Fordisc [43], small sample sizes for the Hispanic reference groups are potentially at play (reported as n=31 in the help file), as well as antiquated populations from the Terry collection for the American Black reference sample. For Hispanic populations, our current methodologies have failed to capture both diversity in stature within and among Hispanic populations, and secular changes between skeletal populations and more modern cases [61,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Fordisc [43], small sample sizes for the Hispanic reference groups are potentially at play (reported as n=31 in the help file), as well as antiquated populations from the Terry collection for the American Black reference sample. For Hispanic populations, our current methodologies have failed to capture both diversity in stature within and among Hispanic populations, and secular changes between skeletal populations and more modern cases [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…For Hispanic populations, our current methodologies have failed to capture both diversity in stature within and among Hispanic populations, and secular changes between skeletal populations and more modern cases [61,62]. Furthermore, the more commonly used ancestry estimation methods also do not include reference samples that represent many of these groups, yet may often yield acceptable typicality probabilities [64].…”
Section: Stature Estimationmentioning
confidence: 99%
“…Another important contribution to the modern American database is the sample of Southwest Hispanic individuals identified by the Pima County Office of the Medical Examiner (PCOME). Currently the MaMD contains data for 34 identified individuals from the PCOME, a number expected to grow exponentially as that office improves identification strategies for unidentified border crossers (Anderson, ; Anderson & Parks, ; Baker, ; Bartelink, ; Beatrice and Soler, ; Crider, ; Figueroa‐Soto & Spradley, 2013; Fowler and Hughes, ; Fulginiti, ; Galloway, Birkby, Jones, Henry, & Parks, ; Galloway, Birkby, Kahana, & Fulginiti, ; Hefner et al, ; Hinkes, ; Hurst, ; Hughes, Algee‐Hewitt, Reineke, Clausing, & Anderson, ; Martinez, Reineke, Rubio‐Goldsmith, & Parks, ; Reineke and Anderson, ; Soler and Beatrice, ; Spradley, 2014; Spradley, Anderson, & Tise, ; Spradley and Jantz, ; Tise, Kimmerle, & Spradley, ; Tise, Spradley, & Anderson, ;). Unidentified, or circumstantially identified, individuals from the PCOME (n = 120) with data in the MaMD are periodically updated as new identifications are made.…”
Section: A Brief Discussion On Data Funding and The Major Sources Of mentioning
confidence: 99%
“…Only recently have studies sought to produce information estimation criteria for individuals of Mexican nationality. Yet, they have been constrained to the study of sex and ancestry using metric skeletal data from positively identified US-Mexico border crosser fatalities (Fowler and Hughes 2018;Hughes et al 2018;Ross et al 2014;Spradley et al 2015;Spradley et al 2008;Tise et al 2013). Due to the small numbers and lack of demographic information (i.e., true age) for these highly targeted analyses, other parameters requiring osteological estimation, such as age-at-death have not been thoroughly examined and validated against the most well-established aging techniques even for these samples.…”
mentioning
confidence: 99%